Examining individual differences in reading and attentional control networks utilizing an oddball fMRI task - Arrington, C. Nikki (Dev Cogn Neurosci, 2019)
The aim of the current study was to develop an fMRI task capable of characterizing individual differences in reading and attentional domains. Forty-nine students with a range of reading and attentional control abilities completed an event-related fMRI oddball task consisting of printed word and false font stimuli. Reading network activation was assessed by contrasting printed words with false font stimuli. Left inferior frontal gyrus and superior/middle temporal gyrus showed a main effect of stimulus type. The magnitude of the difference in activation between words and false font was correlated with word reading for both regions and reading fluency for superior/middle temporal gyrus. Regions including bilateral middle cingulate, insula and right inferior frontal gyrus showed a main effect of trial type. The difference in activation between oddball and standard trials in the right superior/middle temporal gyrus and left cerebellum was correlated with attentional control measures. Results indicate the task tapped both reading and attentional control resources. Understanding the contribution of the neural networks supporting each of these domains may provide insight into the shared neural deficits underlying the co-morbidity between developmental dyslexia and attention deficit hyperactivity disorder.